Karakteristik Mortalitas Pasien Geriatri Pascaoperasi di ICU RSUP Prof. Dr. R. D. Kandou Manado Periode Juli 2024-Juli 2025 - Laritmas, Sintikhe C. Y.; Kambey, Barry I.; Lalenoh, Diana Ch. (Universitas Sam Ratulangi, 2026)
Abstract: Increased number of elderly population is accompanied by a decline in physiological function and multiple comorbidities, therefore, increases their vulnerability to postoperative complications and mortality. This study aimed to describe the clinical characteristics of postoperative mortality in geriatric patients in the Intensive Care Unit (ICU) at Prof. Dr. R. D. Kandou General Hospital in Manado from July 2024 to July 2025. This was a descriptive and retrospective study using medical records of 119 geriatric patients who met the inclusion criteria. The variables examined included age, gender, comorbidities, type of surgery, and length of hospital stay. The results showed that the pre-elderly group (60-69 years) was the largest group (50.42%). The gender proportion was relatively balanced, with 50.42% female and 49.58% male. Hypertension (60.50%) was the most common comorbidity, while digestive surgery was the most common type of surgery (36.13%). In addition, the majority of patients had a length of stay ≥7 days (57.98%). In conclusion, pre-elderly patients with multiple comorbidities, especially hypertension, as well as those who underwent digestive surgery and had a longer length of stay, were the most common group found in the mortality population of this study. Keywords: geriatric patients; Intensive Care Unit; characteristics; retrospective; mortality Abstrak: Pertambahan populasi lanjut usia, disertai penurunan fungsi fisiologis dan komobiditas multipel, meningkatkan kerentanan mereka terhadap komplikasi pascaoperasi dan mortalitas. Penelitian ini bertujuan menggambarkan karakteristik klinis mortalitas pasien geriatri pascaoperasi di Intensive Care Unit (ICU) RSUP Prof. Dr. R. D. Kandou Manado periode Juli 2024-Juli 2025. Jenis penelitian ialah deskriptif retrospektif, menggunakan data rekam medis 119 pasien geriatri yang memenuhi kriteria inklusi. Variabel yang dikaji meliputi usia, jenis kelamin, komorbiditas, jenis operasi, dan lama rawat inap. Hasil penelitian mendapatkan kelompok pra-lansia (60-69 tahun) merupakan kelompok terbanyak (50,42%). Proporsi jenis kelamin relatif seimbang, yaitu perempuan 50,42% dan laki-laki 49,58%. Hipertensi (60,50%) merupakan komorbiditas tersering, sedangkan bedah digestif menjadi jenis operasi terbanyak (36,13%). Selain itu, mayoritas pasien memiliki lama rawat inap ≥7 hari (57,98%). Simpulan penelitian ini ialah pasien pra-lansia dengan komorbiditas multipel terutama hipertensi, serta yang menjalani operasi digestif dan memiliki lama rawat inap pasien yang lebih panjang merupakan kelompok yang paling banyak ditemukan dalam populasi mortalitas penelitian ini. Kata kunci: pasien geriatri; Intensive Care Unit; karakteristik pasien; mortalitas